The significance of virulence factors in Helicobacter pylori. Issue 7 (28th May 2013) - Shiota, Seiji; Suzuki, Rumiko; Yamaoka, Yoshio
Abstract : Helicobacter pylori ( H. pylori ) infection is linked to various gastroduodenal diseases; however, only a small fraction of these patients develop associated diseases. Despite the high prevalence of H. pylori infection in Africa and South Asia, the incidence of gastric cancer in these areas is much lower than those in other countries. The incidence of gastric cancer tends to decrease from north to south in East Asia. Such geographical differences in the pathology can be explained, at least in part, by the presence of different types of H. pylori virulence factors in addition to host and environmental factors. Virulence factors of H. pylori, such as CagA, VacA, DupA, IceA, OipA and BabA, have been demonstrated to be the predictors of severe clinical outcomes. Interestingly, a meta‐analysis showed that CagA seropositivity was associated with gastric cancer compared with gastritis, even in East Asian countries where almost the strains possess cagA . Another meta‐analysis also confirmed the significance of vacA, dupA and iceA . However, it is possible that additional important pathogenic genes may exist because H. pylori consists of approximately 1600 genes. Despite the advances in our understanding of the development of H. pylori infection‐related diseases, further work is required to clarify the roles of H. pylori virulence factors.